2020
DOI: 10.1111/een.12873
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phenology and abundance of suction‐trapped Diptera from a farmland site in the UK over four decades

Abstract: 1. Recently documented insect declines have caused major concerns and an increased interest in studies using long‐term population‐monitoring data. 2. Samples from a 12.2‐m suction trap were used to examine trends in phenology and abundance of Diptera over four decades. 3. The timing of peak flight has advanced by an average of 17 days, from 23 July in 1974 to 6 July in 2014. 4. The abundance of flies has decreased by 37% over the studied period (from April to September), and peak abundance has decreased by 48%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 55 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Agricultural intensification is likely to have had a negative impact on aerial insect population sizes (Benton et al 2002, Paquette et al 2013, Møller et al 2021, which has been shown to affect the foraging behaviour of another swallow species (Stanton et al 2016). In this study, we found a long-term decline in insect biomass at one of four sites (Hereford), an increase at one site (Rothamsted) and stable populations at two sites, although subsequent analyses have also identified a decline in Diptera abundance (trends in biomass were not tested) at the Rothamsted suction trap (Grabener et al 2020). Swallow population trends were also variable between the four trap sites, although there was no obvious link between trends in insects and Swallows.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Agricultural intensification is likely to have had a negative impact on aerial insect population sizes (Benton et al 2002, Paquette et al 2013, Møller et al 2021, which has been shown to affect the foraging behaviour of another swallow species (Stanton et al 2016). In this study, we found a long-term decline in insect biomass at one of four sites (Hereford), an increase at one site (Rothamsted) and stable populations at two sites, although subsequent analyses have also identified a decline in Diptera abundance (trends in biomass were not tested) at the Rothamsted suction trap (Grabener et al 2020). Swallow population trends were also variable between the four trap sites, although there was no obvious link between trends in insects and Swallows.…”
Section: Discussionmentioning
confidence: 56%
“…Swallow diet is diverse and the response of different insect taxa to environmental change will differ: warming may alter aphid population dynamics (Bell et al 2015) but have a negative impact on Diptera associated with wet soils (Pearce-Higgins 2010, Pearce-Higgins & Morris 2023), both of which form a significant component of Swallow diets. In this study we found that Swallow chick survival was more dependent on the biomass of other insects, largely Diptera, than on aphids, and they may therefore be sensitive to declines in Diptera abundance (Grabener et al 2020). We call for further studies of the contribution that large-scale declines in insect abundance may have had upon insectivore population trends.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The latter included declines of 51% in broadleaf woodland, 43% in the uplands, 44% in urban habitats and 28% in improved grassland from 1968–2016 [ 44 ]. Declines in aerial insect abundance have been reported at some English sites, but not others [ 45 , 46 ]. Overall, it appears that the putative magnitude of earthworm declines suggested by our analysis are similar to that of other declining insect groups in the UK, if less than declines reported from continental Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2000 long‐term research in insects illustrated declines in distribution in well‐studied insects such as butterflies, bumblebees, moths, bees, and flies (Biesmeijer et al, 2006; Bourn & Thomas, 2002; Carvell et al, 2006; Conrad et al, 2006; Shortall et al, 2009). In more recent years, many case studies and reviews prove that the distribution and abundance of many other insect groups have declined by 30%–75% within a few decades (Bell et al, 2020; Dirzo et al, 2014; Fox et al, 2014; Grabener et al, 2020; Hallmann et al, 2017, 2020; Homburg et al, 2019; van Strien et al, 2019). Society realises that these insects are an essential link in the food web, and that they facilitate essential processes such as pollination and nutrient recycling (Habel & Schmitt, 2018; Raven & Wagner, 2021).…”
Section: Introductionmentioning
confidence: 99%